The human lens is capable of trilineage differentiation towards osteo-, chondro-, and adipogenesis—a model for studying cataract pathogenesis - Boix-Lemonche, Gerard; Nagymihaly, Richard M.; Lumi, Xhevat; Petrovski, Goran (Frontiers in Bioengineering and Biotechnology, 2023)
The potential for trilineage differentiation of cells in tissues represents a model for studying disease pathogenesis and regeneration pathways. Human lens trilineage differentiation has not yet been demonstrated, and so has calcification and osteogenic differentiation of human lens epithelial cells in whole human lens. Such changes can pose risks for complications during cataract surgery. Human lens capsules (n=9) from cataract patients undergoing uneventful surgery were trilineage differentiated towards osteogenesis, chondrogenesis and adipogenesis. Furthermore, whole human healthy lenses (n=3) collected from cadaveric eyes were differentiated into bone and characterized by immunohistochemistry. The cells in the human lens capsules were capable of undergoing trilineague differentiation, while the whole human healthy lenses could undergo osteogenesis differentiation, expressiing osteocalcin, collagen I and PEDF. We hereby show an ex vivo model for cataract formation through different stages of opacification, as well as provide in vivo evidence from patients undergoing calcified lens extraction with bone-like consistency.